2017
DOI: 10.1111/apa.14047
|View full text |Cite
|
Sign up to set email alerts
|

Children who commute to school unaccompanied have greater autonomy and perceptions of safety

Abstract: Older children who actively commuted to school unaccompanied had better safety perceptions than other children in this sample of children aged 6-12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
2
19
0
3
Order By: Relevance
“…Other determinants such as distance, safety or neighborhood attributes might be more important than weather conditions in that choice. Independence in the decision on mode of commuting increases in adolescents because independent mobility increases with age . Adolescents make a decision about their mode of commuting to school taking into account the distance, safety, or weather factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other determinants such as distance, safety or neighborhood attributes might be more important than weather conditions in that choice. Independence in the decision on mode of commuting increases in adolescents because independent mobility increases with age . Adolescents make a decision about their mode of commuting to school taking into account the distance, safety, or weather factors.…”
Section: Discussionmentioning
confidence: 99%
“…Independence in the decision on mode of commuting increases in adolescents because independent mobility increases with age. 37,39 Adolescents make a decision about their mode of commuting to school taking into account the distance, safety, or weather factors. Accordingly, Simons et al (2013) concluded that weather (as well as travel time, autonomy, and social support among others) is a determinant in the decision on mode of commuting in older adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted from 2007 to 2008, 50% of adolescents displayed ACS, mainly walking [25], whereas another study found that 60% of Spanish children aged 8-15 years old showed ACS [26]. The differences between children and adolescents could be because children are less independent than adolescents to choose the mode of commuting to school, since they are often guided by their parents [26]. In addition, the difficulty to compare both studies should be noted, given the different types of assessments conducted (i.e., GPS vs. self-reported questionnaires).…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, walking was the main mode of commuting, accounting for 50% of the trips to and from school. Similarly, in a study conducted from 2007 to 2008, 50% of adolescents displayed ACS, mainly walking [25], whereas another study found that 60% of Spanish children aged 8-15 years old showed ACS [26]. The differences between children and adolescents could be because children are less independent than adolescents to choose the mode of commuting to school, since they are often guided by their parents [26].…”
Section: Discussionmentioning
confidence: 97%
“…Distintas disciplinas (sociología, antropología, geografía, psicología) se han interesado en las experiencias y rutinas de los niños y adolescentes en los espacios urbanos. Estos estudios, centrados principalmente en las dimensiones geográficas y espaciales, han señalado la naturaleza porosa del espacio entre las dos esferas de influencia en la infancia: el hogar y la escuela (Herrador-Colmenero et al, 2017), una porosidad que resalta el hecho de que el espacio no es una entidad claramente delimitada. Por el contrario, sus límites borrosos favorecen los intercambios recíprocos entre el individuo y los diferentes espacios que cruza, lo que, a su vez, contribuye a su desarrollo psicológico y social (James y Prout, 1997).…”
Section: Espacios Jóvenes Y Sus Palabrasunclassified